Establishing School/Madrasah Leadership And Management Based On Information Technology - Agryanda, Agryanda (Universitas Pakuan, 2023)
The rapid advancement of technology has positively impacted various aspects of society. The increasing interest in utilizing information technology advancements by individuals and organizations has become a helpful tool facilitating daily activities. In the context of education, educational institutions have diverse needs in running and managing their operations. One of these needs is to provide access to data and information obtained through the processes of collection, recording, processing, duplication, storage, and transmission until the information is received by decision-makers. If such activities are done manually, efficiency is likely to be compromised. Therefore, school/madrasah leaders need to have a deep understanding of the concepts of big data, analytics, and related technologies to optimize timely and accurate decision-making processes. In this context, leadership and management of schools/madrasahs based on information technology also present new challenges. The data collection for this research employs library research, and content analysis is used as a data analysis technique to examine and understand the content of literature materials. This study aims to address IT-based leadership in the educational context, emphasizing that it goes beyond the ability to operate software or hardware. It focuses on the capacity to leverage IT to design relevant learning strategies and the ability to influence, encourage, guide, direct, and mobilize the entire school community to engage in the development of learning in the digital era. By understanding and applying information technology-based management concepts, school leaders can lead their institutions toward better educational effectiveness and quality.